The Oral-Skin Axis in Autoinflammation: A Case Report of Severe Refractory Generalized Pustular Psoriasis (GPP) Resolved by Comprehensive Periodontal Intervention - Ni Putu Wina Widyastuti; Prima Sanjiwani Saraswati Sudarsa; Herman Saputra; Handelia Phinari; Luh Putu Venny Cempaka Sari; Kevin Jonathan Djuanda; Mario Korwa (HM Publisher, 2026)
Background: Generalized pustular psoriasis (GPP) is a severe, IL-36-driven autoinflammatory dermatosis, distinct from psoriasis vulgaris. Chronic periodontitis (CP) is a dysbiotic inflammatory disease sharing pathogenic pathways (IL-1, IL-17). An